فدرالية جبهة التحرير الوطني بفرنسا ودورها في تأطير النشاط الثوري للمهاجرين الجزائريين (El-Wahat Journal for Research and Studies, 2021)
ملخص:لم تكن الثورة الجزائرية ثورة نخبوية تحتكرها فئة معينة دون غيرها، فقد راعت في فلسفتها الاستفادة من الجميع، شعوبا وحكومات، مؤيدين لها أو مناوئين، من داخل الوطن أو من خارجه، فحيثما كانت مصلحة الثورة يمم قادتها وجهتهم صوبها، فلم يتخندقوا مع أيديولوجية ضد أخرى، ولا ناصروا نظاما ضد غريمه، لأن ضرورة المصلحة تقتضي حشد الدعم لا اتخاذ المواقف، هكذا فرق قادة الثورة الذين عركتهم الأيام والسنون بين احتياجات الثورة التي يخوضون غمارها ومواقف الدولة التي يعملون على انبعاثها من جديد، وفي هذا الاطار عمل قادة الثورة على إشراك جميع شرائج المجتمع في انتصارها من عمال، طلبة، فلاحين وغيرهم، سواء داخل الجزائر أو خارجها، وفي طليعة ذلك نجد الجالية الجزائرية في فرنسا التي كانت لها مساهمة معتبرة في الثورة . تحاول هذه الدراسة إماطة اللثام عن الدور الذي لعبته فدرالية جبهة التحرير الوطني بفرنسا أثناء الثورة، ودورها في تأطير المهاجرين الجزائريين.الكلمات الدالة:فدرالية جبهة التحرير الوطني، المهاجرون الجزائريون، الثورة الجزائرية، السلطات الاستعمارية، جبهة التحرير الوطنيAbstract:The Algerian revolution was not an elite revolution that was taken over by a particular group of people and not any others. In its philosophy, it has taken into account to benefit from everything and everybody including, supporters and opponents whether inside or outside the country. Its leaders has directed their attention towards wherever the interest of the revolution was, they did not ditch with an ideology against another and they did not support a certain regime against its rivals, because the necessity of the interest requires mobilizing support, not taking positions.   The leaders of the revolution worked to involve all sections of society in its victory, including workers, students, farmers and others, both inside and outside Algeria and at the front lines of that we find the Algerian community in France that was valuable Additive to this revolution. This study aims to unveil the role of the Federal in supporting the revolution, and in supervising the Algerian immigrants.Keywords:The Federation of the Algerian revolution,Colonial powers, National Liberation, Front, Algerian immigrants